PENGARUH PUBLIKASI LAPORAN KEUANGAN TERHADAP REAKSI INVESTOR (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2014-2015) - Gladys Bella Novenna Rettob (Jurnal Ilmiah Mahasiswa FEB, 2015)
Investor’s reactions are responds showed by investor towards information given by the company. If the announcement contains informations then it is expected that the informations accepted properly by the investor and giving a certain reaction such as stock trading volume and stock price movement. Information given by the company may be in the form of accounting informations namely financial report. Financial report is a summary of accounting registration made by company management as an accountability act and as one of consideration substances for investor to conduct investation. This research employs event study to examine information substances in financial report. This research is conducted with observation window throughout 11 days of observation. The sample from this research is manufacture company which is registered in stock exchange period 2014-2015. The amount of samples in this research are 70 companies. Hypothesis examination in this research is using Wilcoxon test. Hypothesis examination outcome in this research statistically giving result that is no differences towards investor’s reaction in form of the average of trading volume activity and abnormal return at the time of before nor after the publication of financial report.Keywords: Event Study, Investor’s Reaction.